A Agroecologia tem rosto de mulher: as experiências das mulheres camponesas do município do Crato - Ceará e suas estratégias para enfrentar a fome - Araújo, Bruna Dayane Xavier de (2022)
Food is a vital source for human beings. Food is a central axis to understand the networks of sociability and is one of the primary pillars in the construction of our humanity. In this context of food, the objective of this thesis was to investigate the political role and agroecological praxis developed by peasant women in the municipality of Crato, located in the south of the state of Ceará. In order to analyze the process in which they develop agroecology and, at the same time, are transformed by it. These women have, in their life stories, the struggle for the right to land, initiatives to create agroecosystems, implementation of agroecological fairs, participation in unions and links with popular culture. They have been building experiences of autonomy and reinvention of the way of living with the territory, with capacities to interfere and transform the agrifood system at the local level. The analytical categories that underpin this study are: Hunger, Territory, Peasant Women, Agroecology and Food Sovereignty. This allowed for a deeper understanding of the totality in which the issue of food is constructed. Hunger is seen, in this research, as a social and collective phenomenon that affects certain social groups in a territory, characterized as endemic, epidemic, hidden, and partial hunger. The food understood as a fragment of the territory is also the result of social relations, for example, of peasant resistances in their spatial clippings. In order to analyze this process, a bibliographical survey was carried out, as well as documental research and field work, by means of photographic, audio, and video records and interviews that aimed at capturing the life narratives of these peasant women. The city of Crato, the locus of the research, is located in the Cariri region of Ceará. This region has several conflicts resulting from development projects and distinct cosmovisions for the territory, showing us that the class struggle-territory relationship is inseparable. This region coexists, in a dialectic and contradictory way, with plenty, hunger, abundance, and the normalization of social inequalities. It is in this context that peasant women have been developing relevant agroecological experiences. In parallel, to the hegemonic agricultural model, peasant women produce a more diversified agriculture, free of pesticides, with quality and more accessibility to the population. In addition, these experiences strengthen popular knowledge, gender equity relations, and bring elements to the debate on food autonomy and sovereignty.